POWDER INJECTION MOLDING OF CU/GRAPHENE COMPOSITE: RHEOLOGICAL PROPERTIES - Rashid, M.O.A.; Mohamad, N.; Sulong, A.B.; Kadiman, N.N.; Ukwueze, B.E. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Powder injection molding (PIM) comes with several benefits, namely, great precision, low cost suitability and high production rate, for metal and ceramics. Mostly compacting and coating process were used for metal composite and only a few studies report the use of an injection process as their processing technique, due to that only few data available related to rheological behavior of Cu/GNp composite. Feedstock rheological behavior needs to be determined in order to avoid any non-homogeneous mixture between powder and binder that may result in powder and binder separation during the injection molding process. This study is focused on rheological properties of Cu/GNp composite produced through PIM. The critical powder loading percentage obtained are 64 % for all 3 compositions; Cu/GNps (0.5, 1.0 and 1.5) vol.%. The optimum powder loading chosen for this study is 62% and within 2-5% below than critical powder loading. For rheological studies Shimadzu Flow Tester CFT-500D capillary rheometer was used. Based on the obtained result, it shows that the overall shear rate and viscosity are within the PIM process recommended range. All tested composition shows pseudoplastic behavior and green part was successfully injected without any physical defect.